Bishop Apollos (Belyaev) and Development of Vyatka Diocese in 1866—1885 - M. Yu. Polovnikova (Научный диалог)
Using mainly historical-comparative and historical-genetic methods, the issue of the development of the Vyatka and Slobodsk dioceses, which coincides within the borders with the Vyatka province, under Bishop Apollos (Belyaev), is considered in the article. The author pays special attention to the process of organizing religious, educational and missionary activities, and up to the appointment of Bishop Apollos, the results of this work were insignificant. The novelty of the research lies in the fact that for the first time it comprehensively examines the activities of the Vyatka Bishop Apollos in terms of the implementation of a nationwide religious course, which included active educational and missionary work of the local clergy. Under Bishop Apollos, to increase the influence of the clergy on the local population, including the Old Believers and non-Orthodox, important transformations were carried out: a separate vicariate was allocated in the diocese, the Vyatka Committee of the Orthodox Missionary Society and the Vyatka Brotherhood of St. Nicholas the Wonderworker were opened, and the work of the local clergy was also generally reorganized. This gave the first positive results in strengthening the position of the Russian Orthodox Church among the local population of the Vyatka diocese.